Safety Management for Service Delivery in Rivers State Secondary Schools (Global Journal of Human-Social Science, 2017)
This study investigated safety management for service delivery in secondary schools in Rivers State. Three research questions and three hypotheses guided the study. The study was guided by Theory of Foundation for Safety Management. The study adopted a descriptive survey design comprising all the 247 government senior secondary schools in the state with 6,890 principals and teachers. A sample size of 2,100 respondents was drawn using stratified random sampling technique representing 30.5% of the population. This included 110 principals and 1,990 teaching staff. The instrument used was questionnaire titled "Safety Management of Secondary Schools' Questionnaire (SMSSQ)" developed by the researchers. The questionnaire was validated and the reliability calculated with Pearson's Product Moment Correlation yielded an index of 0.81. Mean scores and standard deviation were used to answer the research questions.
Keywords: management of safety; service delivery; secondary schools